On the role of pairing modes in the (h 9/2 3-multiplet of 209 Bi. - Bortignon, D. F.; Broglia,R. A.; Bés, Daniel; Liotta, R.; Paar, V. (North Holland Publishing, 1976)
Fil: Bortignon, D. F. The Niels Bohr lnstitute. University of Copenhagen; Dinamarca